Thucydides’ Ἔργα - Rawlings, Hunter R. (Histos, 2021)
This paper argues that in order to understand Thucydides 1.22, his well-known chapter on methodology, we need to grasp the central message of 1.20–3. In this passage, unified by the ‘Herodotean’ word ἔργα, which he adapts for his novel purpose, Thucydides claims that he has, through careful and critical research, reproduced precisely in writing the deeds done in ‘his war’. He explicitly does not claim such accuracy for his speeches, nor for his pre-war excursuses, such as the Archaeology and the Pentekontaetia. His phrase for this kind of rhetorically sophisticated ‘approximation’ of the truth is ἀγώνισμα ἐς τὸ παραχρῆμα ἀκούειν.